Unprecedented Regioselective Deuterium‐Incorporation of Alkyltrimethylammonium Chlorides and Raman Analysis. Issue 3 (3rd February 2023) - Sawama, Yoshinari; Matsuda, Takumi; Moriyama, Shogo; Ban, Kazuho; Fujioka, Hiroyoshi; Kamiya, Mako; Shou, Jingwen; Ozeki, Yasuyuki; Akai, Shuji; Sajiki, Hironao
Abstract: Alkyltrimethylammonium chlorides (ATACs) are widely utilized as cationic surfactants in various scientific fields. Furthermore, deuterium‐incorporated compounds can be powerful tools for elucidating the complicated morphologies of molecules with high molecular weights. Dodecyltrimethylammonium chloride (DTAC), as a representative ATAC, underwent the regioselective multi‐deuteration of alkylamine moiety, except for α and β ‐positions. Deuteration was performed under Pt/C and Ru/C‐catalyzed conditions in 2‐PrOH and D2 O. The stimulated Raman scattering (SRS) revealed the specific signals of multi‐deuterated DTAC in the silent region. Abstract : Dodecyltrimethylammonium chloride (DTAC), as a representative ATAC, underwent the regioselective multi‐deuteration of alkylamine moiety, except for α and β ‐positions. Deuteration was performed under Pt/C and Ru/C‐catalyzed conditions in 2‐PrOH and D2 O. The stimulated Raman scattering (SRS) revealed the specific signals of multi‐deuterated DTAC in the silent region.